The biophysicist's guide to the bacterial flagellar motor. Issue 2 (4th March 2017) - Nirody, Jasmine A.; Sun, Yi-Ren; Lo, Chien-Jung
Graphical Abstract: Abstract: The bacterial flagellar motor (BFM) is a rotary electric nanomachine that drives swimming in a wide variety of bacterial species. There have been many milestones, both theoretical and experimental, that have furthered our understanding of this tiny motor since the first swimming flagellated bacteria was observed. In this article, we review some of these key events, and illustrate how theory and experiment intertwine and inform each other towards a deeper understanding of the BFM's mechanism. Experimental results have inspired theoreticians to build and update models, while model predictions have served to guide experimental design. This cooperative and mutually beneficial communication is a prime example of the interdisciplinary and open nature of modern scientific research.